The Effect of Service Quality, Price, and Product Completeness on Customer Satisfaction at Berkah Mandiri Mojo Supermarket - Visesa, Yayang Nabia; Bhirawa, Sigit Wisnu Setya (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim: The purpose of this study was to analyze the effect of service quality, price and product completeness partially and simultaneously on customer satisfaction at Berkah Mandiri Mojo supermarket. Design/Method/Approach: This research uses a quantitative approach and the technique used is causality. The population of this research is all consumers of Berkah Mandiri Mojo supermarket and the sample used in the study was 100 respondents and analyzed using multiple linear regression methods. Research Finding: The results of this study are service quality and product completeness partially have a positive and significant effect. Partially price has no positive and significant effect. While simultaneously service quality, price and product completeness have a significant effect on customer satisfaction. Theoretical contribution/Originality: This research provides understanding and insight related to service quality, price and product completeness to achieve success in the market. Practitionel/Policy implication: Can be useful for marketing services and products in stores or supermarkets Research limitation: the limitation of this study is the difficulty of sampling because respondents do not have enough time for us to give questionnaires.